THE INFLUENCE OF RAW MATERIAL QUALITY AND PRICE ON CONSUMER DECISIONS BUY BROILER PRODUCTS 1 AT PT. INDOJAYA AGRINUSA MEDAN - Purnama Sari, Dian; Ikhawana, Hablil (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
This study aims to determine whether the quality of raw materials and prices have a significant effect on consumer decisions in buying broiler 1 products at PT. Indojaya Agrinusa Medan and how much influence the quality of raw materials and prices have on consumer decisions in buying broiler 1 products at PT. Indojaya Agrinus Medan. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the regression results of the primary data processed using SPSS 18, the multiple linear regression equation is obtained as follows: Y = 4.234 + 0.109 X1 - 0.781 X2. Partially, the raw material quality variable (X1) has a significant influence on purchasing decisions, as evidenced by the t count > t table (8.977 > 2.012). Meanwhile, the price variable (X2) does not have a significant effect on purchasing decisions, as evidenced by the value of t count < t table (1.821 < 2.012). Simultaneously, raw material quality (X1) and price (X2) variables have a significant influence on purchasing decisions. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (26.080 > 3.20). Raw material quality (X1) and price (X2) variables are able to contribute to the purchasing decision variable by 68.1% while the remaining 31.9% is influenced by other variables not examined in this study. From the conclusion above,